Pengaruh Transfer Pricing, Return On Asset, Financial Leverage, Firm Size Terhadap Income Shifting Pada Perusahaan Consumer Goods Yang Listed Di BEI Periode 2014-2019 - Kiki Amelia; Bahtiar Usman (HK-Publishing, 2022)
AbstractThe purpose of this research was examined and analyzed the effect of transfer pricing on income shifting. The purpose of this research was examined and analyzed the effect of return on assets on income shifting. The purpose of this research was examined and analyzed the effect of financial leverage on income shifting. The purpose of this research was examined and analyzed the effect of firm size on income shifting. The purpose of this research was examined and analyzed the effect of transfer pricing, return on assets, financial leverage, and firm size on income shifting. Purposive sampling is a sampling technique by determining certain criteria. Panel data analysis and hypotheses were tested using Eviews. The results showed that there was no positive relationship between Transfer Pricing and Income Shifting. There is no positive effect on income shifting. There is no effect of Financial Leverage on Income Shifting. This is because the company is able to pay off obligations according to maturity with their capital so that the company does not experience financial difficulties which makes the company's risk smaller so that management does not need to smooth out income. There is an effect of firm size on income Shifting proven and accepted.Keyword: Transfer Pricing, Return On Asset, Financial Leverage, dan Firm Size, Income Shifting. AbstrakTujuan dari penelitian ini adalah Untuk meneliti dan menganalisis pengaruh transfer pricing terhadap income shifting. Untuk meneliti dan menganalisis pengaruh return on asset terhadap income shifting. Untuk meneliti dan menganalisis pengaruh financial leverage terhadap income shifting. Untuk meneliti dan menganalisis pengaruh firm size terhadap income shifting. Untuk meneliti dan menganalisis pengaruh transfer pricing, return on asset, financial leverage, dan firm size terhadap income shifting. Purposive sampling merupakan teknik pengambilan sampel dengan menentukan kriteria tertentu. Analisis data panel dan hipotesis diuji dengan menggunakan Eviews. Hasil penelitian menunjukkan bahwa tidak terdapat hubungan positif antara Transfer Pricing terhadap Income Shifting. Tidak terdapat pengaruh positif terhadap income Shifting. Tidak terdapat pengaruh Financial Leverage terhadap Income Shifting. Hal ini dikarenakan perusahaan mampu melunasi kewajiban sesuai masa jatuh tempo dengan modal yang dimiliki sehingga perusahaan tidak mengalami kesulitan keuangan yang membuat risiko perusahaan menjadi kecil sehingga manajemen tidak perlu melakukan perataan laba. Terdapat pengaruh firm size terhadap income Shifting terbukti dan diterima. Kata Kunci: Transfer Pricing, Return On Asset, Financial Leverage, Dan Firm Size, Income Shifting.